2022
DOI: 10.1039/d2tc02911a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of inorganic carrier transport layer materials and interfaces in emerging perovskite solar cells

Abstract: In the recent decade, the organic-inorganic hybrid and metal halide perovskite materials have shown tremendous property tunability and capacity to harvest solar energy efficiently via conceptually new solar cell architectures....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 597 publications
(676 reference statements)
1
19
0
1
Order By: Relevance
“…The functions of the transport layers mainly include the following four points: rst, adjusting the electrode work function to form an ohmic contact between the electrode and the photosensitive layer; second, improving the directional transmission of electrons and holes, and reducing the interface recombination rate of carriers; third, facilitating the enhancement of the photon capture ability of the photosensitive layer; fourth, improving the stability of FSCs. 146,147 Therefore, optimizing the preparation process to control the compositions and structures of the transport layers is crucial to improve the photovoltaic performance of FSCs. The most popular material used for constructing ETL layers in FSCs is TiO 2 , which can support the photosensitive layer, promote the extraction of interface charges, and reduce the effect of hysteresis.…”
Section: Strategies To Enhance the Extraction And Transport Of Photog...mentioning
confidence: 99%
“…The functions of the transport layers mainly include the following four points: rst, adjusting the electrode work function to form an ohmic contact between the electrode and the photosensitive layer; second, improving the directional transmission of electrons and holes, and reducing the interface recombination rate of carriers; third, facilitating the enhancement of the photon capture ability of the photosensitive layer; fourth, improving the stability of FSCs. 146,147 Therefore, optimizing the preparation process to control the compositions and structures of the transport layers is crucial to improve the photovoltaic performance of FSCs. The most popular material used for constructing ETL layers in FSCs is TiO 2 , which can support the photosensitive layer, promote the extraction of interface charges, and reduce the effect of hysteresis.…”
Section: Strategies To Enhance the Extraction And Transport Of Photog...mentioning
confidence: 99%
“…3−5 To date, highly efficient PSCs are achieved on the regular n−i−p device architecture, in which the surface morphology and chemistry of the electron transport layer (ETL) can affect the deposition and quality of the perovskite layer. 6,7 Among various n-type semiconducting materials, SnO 2 stands out as a promising ETL in n−i−p PSCs due to its low-temperature processable synthesis, high optical transmittance, superior electron mobility, and proper band energy alignment with the perovskites. 8 However, the presence of defects (e.g., oxygen vacancy defects) and dangling bonds on the surface of SnO 2 can enhance the nonradiative recombination at the SnO 2 /perovskite interface, affecting device performance and stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since the past decade, three-dimensional hybrid organic–inorganic lead halide perovskites (LHPs) have inspired scientists in the field of optoelectronic devices due to their extraordinary optoelectronic properties. , There is particular attention on the application of LHPs as light absorber materials in the next generation of thin film photovoltaic technology, and so-called perovskite solar cells (PSCs) have emerged as a “rising star” due to their high-power conversion efficiency (PCE) exceeding 25%, low cost, and facile fabrication techniques. To date, highly efficient PSCs are achieved on the regular n–i–p device architecture, in which the surface morphology and chemistry of the electron transport layer (ETL) can affect the deposition and quality of the perovskite layer. , Among various n-type semiconducting materials, SnO 2 stands out as a promising ETL in n–i–p PSCs due to its low-temperature processable synthesis, high optical transmittance, superior electron mobility, and proper band energy alignment with the perovskites . However, the presence of defects (e.g., oxygen vacancy defects) and dangling bonds on the surface of SnO 2 can enhance the nonradiative recombination at the SnO 2 /perovskite interface, affecting device performance and stability. , In this context, many strategies have been undertaken to passivate the surface defects of SnO 2 ETLs to enhance the device’s photovoltaic performance and stability. This includes doping of the SnO 2 ETL with various metal ions and interface modification with ionic salts, , organic molecules, , polymers, self-assembled molecules, or carbon materials …”
Section: Introductionmentioning
confidence: 99%
“…The decent optoelectronic properties of perovskites deliver competitive power conversion efficiency (PCE) to traditional silicon solar cells. Meantime, various charge transport layers have been tried for the efficiency and stability improvement of the PSCs. Perhaps, PSC technology is still far behind the PCE defined by the Shockley–Queisser (S–Q) limit for a perovskite absorber possessing a 1.6 eV band gap as a result of the severe non-radiative recombinations. It is found that the surface defects present at grain boundaries (GBs) and within the bulk act as recombination centers. , Notably, surface defects create non-favorable band bending at the perovskite/charge transport layer (CTL) interface, which affects the open-circuit voltage ( V OC ), preventing the thermodynamically predicted V OC deficit values (0.27 eV) from being achieved. , Further, defect-mediated ion migration and moisture penetration through the GBs trigger perovskite degradation, resulting in the poor stability of the PSCs. Hence, defect passivation of perovskites is of great importance to improve the overall performance of PSCs.…”
Section: Introductionmentioning
confidence: 99%